EKSISTENSI PEKERJA PEREMPUAN (ISTRI) PADA SEKTOR INFORMAL DALAM MENINGKATKAN KESEJAHTERAAN KELUARGA (Studi Kelurahan Abeli Kecamatan Abeli Kota Kendari) - Setiawan, Thamrin; Kasim, Syaifuddin S.; Yusuf, Bakri (Universitas Halu Oleo, 2020)
This study aims to determine the existence of women workers in the informal sector in improving family welfare in Abeli Village, Abeli District, Kendari City, to find out the driving factors and inhibitors of the existence of women workers (wives) in the informal sector in Abeli Village, Abeli District, Kendari City, and the welfare conditions of workers' families woman (wife) in the informal sector in Abeli Kacamatan Abeli Kelurahan of Kendari City. This type of research used in this research is descriptive qualitative research with data collection techniques, namely interviews, observation and documentation. The existence of female workers (wives) in the informal sector in improving family welfare in Abeli Sub-District Abeli District of Kendari City was influenced by several reasons including not requiring high education, the unavailability of jobs in accordance with the level of education, the ability to divide time between work and take care of the household and the social system applied by the community give equal roles between men and women in the workforce. Factors driving the existence of female workers (wives) in the informal sector in Abeli Sub-district, Abeli District, Kendari City include motivation to increase family income and for an economy that does not depend on husbands, while factors inhibiting the existence of women workers (wives) in the informal sector in increasing family welfare in Abeli Sub-district Abeli District of Kendari City is age. As for the family welfare conditions of female workers (wives) in the informal sector in Abeli Sub-District, Abeli District has been fulfilled. This can be seen from the fulfillment of material needs, namely clothing, food and shelter needs. Fulfillment of mental / spiritual needs, namely the spiritual needs of family members and the fulfillment of social needs, namely the need for feeling accepted by the community.